'Suffer the little children' : national and international dimensions of child poverty and public policy - Yeakey, Carol Camp; Richardson, Jeanita W., 1957-; Brooks-Buck, Judith (Advances in education in diverse communities, 2006)
This volume examines the burden of poverty that children and young adults disproportionately share throughout the world. Contributions from international researchers examine some of the profound precursor issues that serve to inhibit the chances of children and young adults to education and social mobility in an international context. Issues such as housing and homelessness, family income, maternal and child health, child care, hunger, adolescent pregnancy, violence by and against children, the impact of war and famine, various forms of social deviance and early childhood education are investigated. The volume also examines the social, political and economic contexts in which poverty occurs, utilizing various theoretical perspectives by which to view issues such as human rights, social development and social cohesion in developing, emerging and transitional societies. Implicit thoughout the volume are the decisions and non-decisions of governments as they confront issues of growing poverty and the repercussions of that poverty for future generations.